2018
DOI: 10.4236/etsn.2018.73003
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Radiographic Anatomy of Wrist in Chinese Population

Abstract: In wrist pathology, there is a need to establish the normal range of radiographic measurement parameters. Previous study showed that the contralateral wrist might not be valid as a reference for all parameters. There is a lack of literature describing the normal range of wrist radiographic parameters in literature. As a result, a retrospective study was carried out. Patients who underwent standard wrist x-rays during the period February 2012 to February 2013 (one single year) were retrospectively reviewed. 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[12][13][14][15][16] Our study demonstrated capitate length to be 22.3 AE 2.3 which was comparable to various studies in the literature (►Table 4). [12][13][14][15][16] In the studies conducted by Tang et al, 17 Jafari et al, 12 and Vaezi et al, 13 males exhibited significantly greater carpal height, third metacarpal height, and capitate length compared to females. Notably, our study also demonstrated higher values of the above parameter in males compared to females (p < 0.001) with no difference across the age group.…”
Section: Carpal Height Ratio and Its Determinantsmentioning
confidence: 99%
“…[12][13][14][15][16] Our study demonstrated capitate length to be 22.3 AE 2.3 which was comparable to various studies in the literature (►Table 4). [12][13][14][15][16] In the studies conducted by Tang et al, 17 Jafari et al, 12 and Vaezi et al, 13 males exhibited significantly greater carpal height, third metacarpal height, and capitate length compared to females. Notably, our study also demonstrated higher values of the above parameter in males compared to females (p < 0.001) with no difference across the age group.…”
Section: Carpal Height Ratio and Its Determinantsmentioning
confidence: 99%